Pengembangan Handmade Masker Untuk Pemberdayaan Ekonomi Masyarakat Gresik Menghadapi Pandemi Covid-19 - Darni; Udjang Pairin; Surana; Latif Nur Hasan; Noviyanti; Yuni Lestari (LPPM Universitas Yudharta Pasuruan, 2020)
The COVID-19 pandemic has spread to all countries in the world. It is not only the nature of the corona virus that has extraordinary spreadability, but this viral pandemic also has an extraordinary impact on all sectors of life. The drastic decline in income, especially for the middle to lower class, was the biggest hit, starting from the loss of income, the non-return of capital, to layoffs. So many government policies have been issued as government strategies in preventing the spread, handling, and efforts to break the chain of COVID-19. Appeals have been issued by the central government to remain calm amidst these extremely difficult circumstances. The word